The Importance of Soft Skills Training to Improve the Quality of Political Party Cadres - Badriawan, Anike Suci (Technium Social Sciences Journal, 2021)
Cadre formation in political parties is very important and determines the quality of human resources capable of making a real contribution to the joint efforts of all elements of the nation building. Leadership and regeneration are two things that are interrelated in organisational development. Regeneration is also very important in an organisation because it is a form of efforts to support the formation of personality integrity and the ability to move others intensively so that a quality leader can be achieved. For this reason, every political party has the duty to provide education and training for its cadres. This research is aimed at answering the questions of how to implement education and training for cadres of political parties, and what soft skills are urgently needed by cadres of political parties in order to improve their quality. This is a qualitative research with a case study approach. Data collection was carried out by semi-structured interviews with political party cadres as well as with community members. This research proves that quality soft skills training for political party cadres which consists of intrapersonal and interpersonal skills is demanding. Intrapersonal skills are mainly related to emotional intelligence and ethical issues. Meanwhile, interpersonal skills cover the ability of communication, leadership skills, thinking skills and problem solving skills.